Three new species of scale mites (Acari: Pterygosomatidae) parasitizing Agama sankaranica (Sauria: Agamidae) - Fajfer, Monika (Zootaxa, 2013)
Three new species of pterygosomatid mites Pterygosoma engai sp. nov. P. indare sp. nov. and P. olape sp. nov. (Acari: Pterygosomatidae) are described from the agamid lizard Agama sankaranica (Sauria: Agamidae) from Kenya. P. engai sp. nov. is similar to P. annectans circularis Jack, 1962 but in the new species, the anterior paddle–shaped setae with spicules on the apical margin of the idiosomal dorsum and three pairs of the postero-lateral setae are present, setae dm1 are paddle-shaped, peripheral setae and setae dGIV are absent, the pseudoanal setal series is represented by three pairs of setae ps. P. indare sp. nov. is most closely related to P. agamae agamae Peters, 1849 but differs by the absence of eyes and setae dGI, the presence of the flattened hypostomal apex and 12–14 pairs of the peripheral setae and some of them are tapered. P. olape sp. nov. is similar to P. engai sp. nov. but differs by the presence of the hypostome with a smooth rounded apex and 16 pairs of the peripheral setae inserted ventrally, the genital series is represented by one pair of setae g situated ventrally and four pairs of setae ps situated ventrally and terminally.